PENGARUH LATIHAN DRILL DALAM MENINGKATKAN KEMAMPUAN BACKHAND CLEAR PADA ATLET BULUTANGKIS PB ABADI - Pallaya, Danu; Arvan Junaidi, Ilham; Riyoko, Endie (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The background of this study is based on the low backhand clear ability of athletes as seen from the less than optimal power of the shot, the accuracy of the shuttlecock direction, and the consistency of the shot during training and matches. This study aims to determine the effect of drill training on improving the backhand clear ability of PB Abadi badminton athletes. This study used an experimental method with a one-group pretest-posttest design. The population in this study were all 15 PB Abadi Indralaya athletes. The sampling technique used saturated sampling, so that the entire population was used as the research sample. The data collection technique was carried out through a backhand clear ability test before and after being given drill training treatment. Data were analyzed using statistical tests to determine the effect of drill training on improving the backhand clear ability of athletes. The results showed that drill training had a significant effect on improving the backhand clear ability of PB Abadi badminton athletes. This improvement was seen in the aspects of power of the shot, the accuracy of the shuttlecock direction, and the consistency of the athlete's shot after being given structured and repeated drill training treatment. Thus, drill training can be used as an effective training method in improving the backhand clear ability of PB Abadi badminton athletes.